Determinants of diabetic ulcer prevention behavior among patients with diabetes mellitus: Application of the theory of planned behavior - Sholihin, Sholihin; Nadhifah, Eva Luthfiyatun; Surya Putri, Novita (Palembang MediRose Publisher, 2025)
Background: Diabetic ulcer is a common and serious complication of diabetes mellitus (DM), often leading to disability and reduced quality of life. Its incidence increases when patients lack adequate knowledge and skills for prevention. Understanding the behavioral determinants of ulcer prevention is essential for targeted nursing interventions. Objective: To identify determinants of diabetic ulcer prevention behavior among patients with DM based on the Theory of Planned Behavior (TPB). Methods: This cross-sectional study involved 39 patients with DM enrolled in the Puskesmas Klatak Prolanis program, selected through purposive sampling. Data were collected using a TPB-based questionnaire adapted to diabetic ulcer prevention indicators, encompassing attitudes, subjective norms, perceived behavioral control, intentions, and preventive behaviors. Data analysis was performed using Chi-square tests in IBM SPSS 23, with a significance level of ? = 0.05. Results: Most respondents demonstrated positive attitudes (56.4%), low subjective norms (56.4%), low perceived behavioral control (56.4%), and low intentions (53.8%). Preventive behavior was predominantly in the fair category (69.2%). Chi-square analysis revealed significant associations between preventive behavior and attitudes (p = 0.004), subjective norms (p = 0.025), perceived behavioral control (p = 0.028), and intentions (p = 0.046). Conclusion: Attitudes, subjective norms, perceived behavioral control, and intentions significantly influence diabetic ulcer prevention behaviors in patients with DM. Nursing interventions should integrate TPB-based strategies to strengthen positive attitudes, enhance perceived control, and foster supportive social environments, thereby improving preventive practices. Routine early detection of diabetic ulcer signs should be prioritized to reduce the risk of severe complications.